Emergence and dissemination of multidrug-resistant Escherichia coli ST8346 coharboring blaNDM-5 and blaOXA-181 in Southern Taiwan, 2017-2021 - Chia-Hung Tsai; Nan-Yao Lee; Chien-Ming Chao; Chi-Chung Chen; Chih-Cheng Lai; Chung-Han Ho; Yu-Chin Chen; Po-Yu Chen; Hung-Jen Tang; Hung-Jui Chen; Bo-An Su; Hsin-Yu Lai; et al. (Elsevier, 2023)
Background: Enterobacterales carrying blaNDM represent an emerging challenge in treating infectious diseases. In this study, we aimed to investigate the characteristics of blaNDM-producing Enterobacterales from three hospitals in southern Taiwan. Methods: Enterobacterales strains that were nonsusceptible to more than one carbapenem (ertapenem, meropenem, imipenem, or doripenem) were collected from hospitalized patients. Molecular typing for New Delhi metallo-β-lactamase (NDM) and antibiotic susceptibility tests were performed, followed by multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE), and plasmid analysis by PCR-based replicon typing. Results: A total of 1311 carbapenem-nonsusceptible Enterobacterales were isolated from 2017 to 2021. blaNDM-encoding genes were detected in 108 isolates, with 53 (49.1%) harboring blaNDM-1 and 55 (50.9%) harboring blaNDM-5. The rate of blaNDM-1 detection among isolates decreased to 2% in 2021. However, the rate of E. coli harboring blaNDM-5 increased from 1% to 12% of total isolates during the study period. Of 47 NDM-5-positive E. coli isolates, 44 (93.6%) were ST8346 with high genetic relatedness. E. coli ST8346 isolates showed high-level resistance to both carbapenems and aminoglycosides. Most (38 out of 47, 80.9%) blaNDM-5-harboring E. coli isolates co-harbored blaOXA-181. We analyzed the regions harboring blaNDM-5 in E. coli ST8346 via PCR amplification. blaNDM-5 and blaOXA-181 were located on two separate plasmids, IncF and IncX3, respectively. Conclusion: The dissemination of E. coli ST8346 caused an increase in blaNDM-5 and blaOXA-181 co-harboring Enterobacterales in southern Taiwan, which show high-level resistance to both carbapenems and aminoglycosides. We identified a distinct IncF plasmid encoding blaNDM-5 that has the potential for rapid spread and needs further surveillance.